Singularities of Pyogenic Streptococcal Biofilms – From Formation to Health Implication - Alves-Barroco, Cinthia; Paquete-Ferreira, João; Santos-Silva, Teresa; Fernandes, Alexandra R. (Frontiers in Microbiology, 2020)
Bacterial biofilms are structured communities of bacterial cells enclosed in a self-produced polymeric matrix that is attached to a surface. These communities are ubiquitous in the environment and occur on all surface types. Microorganisms in biofilms are more resistant to the action of the antimicrobial agents and host defense mechanisms due to several strategies, particularly the presence of a matrix of extracellular polymeric substances and a low growth rate. Biofilms play an important role in the pathogenesis of the genus Streptococcus, contributing to therapy failure and promoting persistent infections. The species of the pyogenic group together with Streptococcus pneumoniae are the major pathogens belonging the genus Streptococcus, and its biofilm growth have been investigated, but insights in the genetic origin of biofilm formation are limited. This chapter summarizes pyogenic streptococci biofilms with details on constitution, formation, and virulence factors associated with formation.